LA POTABILITE DES EAUX DE BOISSON EN SACHET VENDUES AUX ABORDS DES ECOLES PRIMAIRES PUBLIQUES A KISANGANI EN 2016, RD Congo. - Salomon OTOWANGE MANDEFU Y,; Leonard LIFOFA OTAKEWAE,; Dominique NKOY ISOMOLO ISEYANA,; Sylvain MOKILI KANDA ISOMOKELE, (IJRDO- Journal of Educational Research, 2020)
Water is one of the most important commodities in human life because it is said "Water is life’’. Access to drinking water is a guarantee for the fight against many diseases. Our study focused on the potability of the water sold around public primary schools in the city of Kisangani in 2016. The analyzes carried out showed that less than 80% of our respondents wash their hands with soap, the best-opted bagging protocol is tap-bassinet in a bag (54%), utensils are cleaned with soap and water ( 54%), there are utensils reserved only for bagging (61.7%), the opening of the sachets for packaging is done only by hand (75.3%) versus hand and mouth blowing (24.6% ) while the preferred storage location for the water sold is the day cooler (44.4%) while it is kept in combination with other products (54%). We must therefore decry the sale of water sold in the vicinity of public primary schools in Kisangani because it does not respect the water conditioning rules set by the World Health Organization and constitutes a great danger for consumers because of '' a strong presence and density of coliforms (Most likely number / 100ml: 1100) and streptococci (Most likely number / 100ml: 11) contained in this water.